Rethinking Public Housing Through Squatting. The Case of Housing Rights Movements in Rome - Grazioli, Margherita (PARTECIPAZIONE E CONFLITTO, 2021)
This article analyses the contribution of housing squats and Housing Rights Movements (HRMs) in Rome in envisioning a new model of public estates that could respond to the surge and complexification of the post-2008 housing crisis. The first part of the article fleshes out the theoretical and methodological framework for investigating the peculiarities of housing squats in comparison to other forms of housing informality and urban squatting. In the second part, it analyses the development and composition of housing struggles since the post-Second World War. It then details the new demographics of the housing crisis in Rome to provide a framework for the innovation in the HRMs' confrontational politics and demands towards a more comprehensive notion of the 'right to the city'. Their emphasis upon the role of city developers and real estate agents, and the opposition towards the exclusionary nature of contemporary social welfare, have in fact redirected squatting actions towards different urban vacancies that are repurposed for habitation. I conclude by suggesting that these practices prefigure a new model of public housing estates that is economically, environmentally sustainable and socially inclusive, whereby it pivots around use value and commoning.